Genome-wide identification of the PI-PLC gene family in Setaria italica and functional characterization of SiPLC1 in salt stress response - Zhu, Dan; Hu, Xiaobing; Feng, Feng; Tian, Mengqi; Zhang, Yonghu; Chai, Ran; Wen, Rui; Wei, Jianhua; Zhang, Jiewei (Frontiers in Plant Science, 2025)
Foxtail millet (Setaria italica), a typical NADP-ME-type C4 crop, demonstrates superior light-use and water-use efficiencies compared to C3 species. Beyond its photosynthetic edge, it employs a range of stress-resilience mechanisms that optimize growth-defense trade-offs under drought, salinity, or nitrogen scarcity. The combination of high C4 photosynthetic efficiency with extensive stress tolerance is rare among cultivated species, positioning foxtail millet as an ideal model for studying the integration of yield and stress resilience. Phosphoinositide-specific Phospholipase C (PI-PLC) plays a crucial role in lipid- and Ca2+-dependent signaling pathways. In plants, it modulates responses to biotic and abiotic stresses, though the mechanisms remain partially understood. In this study, we identified five PI-PLC-encoding genes in foxtail millet, named SiPLC1-SiPLC5, and analyzed their systematic phylogeny, gene structure, protein characteristics, distribution of the chromosome, collinearity relationship, and cis-acting elements prediction at the promoter region. Phylogenetic analysis revealed that the members of the SiPLCs gene family were divided into three subgroups. Structural analysis that all of them have four conserved motifs and these motifs were evenly distributed. Notably, SiPLC1 harbors an exceptionally large first intron and falls within subgroup II; its protein sequence is highly homologous to AtPLC1 and AtPLC3 of Arabidopsis thaliana (L.) Heynh. and to OsPLC4 of Oryza sativa L. RT-qPCR indicated that SiPLC1 is predominantly expressed in roots during early stem elongation and is significantly upregulated under salt stress. Overexpression of SiPLC1 in Arabidopsis mitigated salt-induced damage, highlighting its critical role in salt-stress signal transduction in foxtail millet.